Effects of the dynamic of regional integration on West Africa's trade - (:unkn) unknown (My University, 2023)
The main purpose of this paper is to examine the effects of the dynamic of regional integration and WTO membership on aggregate bilateral trade of West African countries. Empirical analyses were performed using an augmented structural gravity model on bilateral trade covering the period 1970-2019 and using the PPML estimator with its variants obtained from high-dimensional fixed effects (PPMLHDFE) suggested by Larch et al. (2018). The results show that the dynamic of regional integration in WAEMU significantly increase intra- andextra-bloc trade, whereas in the case of ECOWAS, they imply export trade deversion effects unfavourable to non-member countries. On the other hand, WTO membership diverts intra-bloc trade away from West African countries
Keywords: African Research